A review of the previously monotypic tribe Dibolostethini (Chelodesmidae: Chelodesminae) with description of two new species and a summary of the Chelodesmidae of the Tropical Andes Biodiversity Hotspot - Means, Jackson C.; Bouzan, Rodrigo S.; Iniesta, Luiz Felipe Moretti; Martínez-Torres, Daniela; Vasquez-Valverde, Luisa F.; Brescovit, Antonio D.; Ivanov, Kaloyan (European Journal of Taxonomy, 2023)
The chelodesmid genus Dibolostethus Hoffman, 2009, the sole member of the tribe Dibolostethini, is reviewed. The genus contains the type species D. sicarius Hoffman, 2009 known only from the Los Rios Province, Ecuador, and two new species from the Tropical Andes, D. inopinatus Means, Bouzan & Ivanov sp. nov. from the Morona-Santiago Province, Ecuador and D. kattani Means, Bouzan, Martínez-Torres & Ivanov sp. nov. from the Valle del Cauca Department, Colombia. We redescribe D. sicarius and provide a revised diagnosis of the genus, images of diagnostic morphological characters, and a key to the males of Dibolostethus. In addition, we provide a summary and a distribution map of the Chelodesmidae of the Tropical Andes Biodiversity Hotspot.